Neurology advanced practice providers: A position paper of the American Academy of Neurology. Issue 4 (August 2015) - Schwarz, Heidi B.; Fritz, Joseph V.; Govindarajan, Raghav; Penfold Murray, Rebecca; Boyle, Kathryn B.; Getchius, Thomas S.D.; Freimer, Miriam
Abstract : Summary: There are many factors driving health care reform, including unsustainable costs, poor outcomes, an aging populace, and physician shortages. These issues are particularly relevant to neurology. New reimbursement models are based on value and facilitated by the use of multidisciplinary teams. Integration of advanced practice providers (APPs) into neurology practice offers many advantages with new models of care. Conversely, there are many and varied challenges financially and logistically with these practice models. The American Academy of Neurology has formed a Work Group to address the needs of both neurologists and neurologic APPs and monitor the effect of APPs on quality and cost of neurologic care.